Identification of Piecemeal Degranulation and Vesicular Transport of MBP-1 in Liver-Infiltrating Mouse Eosinophils During Acute Experimental Schistosoma mansoni Infection - Dias, Felipe F.; Amaral, Kátia B.; Malta, Kássia K.; Silva, Thiago P.; Rodrigues, Gabriel S. C.; Rosa, Florence M.; Rodrigues, Gisele O. L.; Costa, Vivian V.; Chiarini-Garcia, Hélio; Weller, Peter F.; Melo, Rossana C. N. (Frontiers in Immunology, 2018)
Eosinophils have been long associated with helminthic infections, although their functions in these diseases remain unclear. During schistosomiasis caused by the trematodeSchistosoma mansoni, eosinophils are specifically recruited and migrate to sites of granulomatous responses where they degranulate. However, little is known about the mechanisms of eosinophil secretion during this disease. Here, we investigated the degranulation patterns, including the cellular mechanisms of major basic protein-1 (MBP-1) release, from inflammatory eosinophils in a mouse model of S. mansoniinfection (acute phase). Fragments of the liver, a major target organ of this disease, were processed for histologic analyses(whole slide imaging), conventional transmission electron microscopy (TEM), and immunonanogold EM using a pre-embedding approach for precise localization of major basic protein 1(MBP-1), a typical cationic protein stored pre-synthesized in eosinophilsecretory (specific) granules. A well-characterized granulomatous inflammatory response with a high number of infiltrating eosinophils surrounding S. mansoni eggs was observed in the livers of infected mice. Moreover, significant elevations in the levels of plasma Th2 cytokines (IL-4, IL-13 and IL-10) and serum enzymes (alanine aminotransferase and aspartate aminotransferase) reflecting altered liver function were detected in response to the infection. TEM quantitative analyses revealed that while 19.1% of eosinophils were intact, most of them showed distinct degranulation processes: cytolysis (13.0%), classical and/or compound exocytosis identified by granule fusions (1.5%), and mainly piecemeal degranulation (PMD) (66.4%), which is mediated by vesicular trafficking. Immunonanogold EM showed a consistent labeling for MBP-1 associated with secretory granules. Most MBP-1-positive granules had PMD features (79.0 ± 4.8%). MBP-1 was also present extracellularly and onvesicles distributed in the cytoplasm and attached to/surrounding the surface of emptying granules. Our data demonstrated that liver-infiltrating mouse eosinophilsare able to degranulate through different secretory processes during acute experimental S. mansoni infections with PMD being the predominant mechanism of eosinophil secretion. This means that a selective secretion of MBP-1is occurring.Moreover, our study demonstrates, for the first time, a vesicular trafficking of MBP-1 within mouse eosinophils elicited by a helminth infection. Vesicle-mediated secretion of MBP-1 may be relevant for the rapid release of small concentrations of MBP-1 under cell activation.